2018
DOI: 10.3389/fneur.2018.00448
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Dynamics Within and Between Resting-State Subnetworks in Juvenile Myoclonic Epilepsy Occur at Multiple Frequency Bands

Abstract: Time-varying connectivity analyses have indicated idiopathic generalized epilepsy (IGE) could cause significant abnormalities in dynamic connective pattern within and between resting-state sub-networks (RSNs). However, previous studies mainly focused on the IGE-induced dynamic changes of functional connectivity (FC) in specific frequency band (0.01–0.08 Hz or 0.01–0.15 Hz), ignoring the changes across different frequency bands. Here, 24 patients with IGE characterized by juvenile myoclonic epilepsy (JME) and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…A recent study reported that patients with GTCS showed enhanced temporal variability of FC in large-scale brain functional networks, with these excessive variability anti-correlated with the duration of disease ( Jia et al, 2020 ). Our previous study also suggested that reduced dynamics within and between RSNs were linked to greater disease severity in JME ( Zhang et al, 2018 ). Taken together, the established associations in this study indicate that the early identified abnormalities in brain networks may be implicated in the progress of the disease, and can be an indication of disrupted developmental processes in JME.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…A recent study reported that patients with GTCS showed enhanced temporal variability of FC in large-scale brain functional networks, with these excessive variability anti-correlated with the duration of disease ( Jia et al, 2020 ). Our previous study also suggested that reduced dynamics within and between RSNs were linked to greater disease severity in JME ( Zhang et al, 2018 ). Taken together, the established associations in this study indicate that the early identified abnormalities in brain networks may be implicated in the progress of the disease, and can be an indication of disrupted developmental processes in JME.…”
Section: Discussionmentioning
confidence: 68%
“…For patients with JME, hyper dynamic characteristics in temporally fluctuating functional networks have been found ( Wang et al, 2019 ). Our previous study also demonstrated altered FC dynamics within and between RSNs, which were associated with the disease severity of JME patients ( Zhang et al, 2018 ). These studies suggested aberrant dynamic connectivity patterns of RSNs, particularly the DMN, are remarkable characteristics in patients with IGE.…”
Section: Introductionmentioning
confidence: 64%
“…Furthermore, in the temporal dimension, the time-varying dynamics of the connections in thalamus-frontal_mid, thalamus-precuneus, precuneus-frontal_mid, and also the frontal_mid-post_central were significantly increased in IGE. The spatial dysconnectivity and the altered FNC dynamics in thalamocortical circuit in epileptic brain have been reported in many studies (O'Muircheartaigh et al, 2012;Kim et al, 2014;Zhang et al, 2018;Qin et al, 2020b). Previous studies have demonstrated the role of thalamus in leading in initiating and maintaining the epileptic activity, which may be involved early or late in the discharge (Tyvaert et al, 2009;Martin-Lopez et al, 2017).…”
Section: Discussionmentioning
confidence: 88%
“…Finally, as mentioned earlier, the eye condition is different in the COBRE and FBIRN datasets. A previous study reported that different eye conditions might modulate DMN dynamics (Zhang et al, 2018), which could explain some differences in the DMN dynamics between the two datasets. State 5 of FBIRN dataset was distinguished from all other states in both datasets by showing higher within-ACC connectivity.…”
Section: Discussionmentioning
confidence: 95%